Long-term follow-up of BVS from a prospective multicenter registry: Impact of a dedicated implantation technique on clinical outcomes. (1st November 2018) - Regazzoli, Damiano; Latib, Azeem; Ezhumalai, Babu; Tanaka, Akihito; Leone, Pier Pasquale; Khan, Sara; Kumar, Vijay; Rastogi, Vishal; Ancona, Marco Bruno; Mangieri, Antonio; Giannini, Francesco; Mitomo, Satoru; et al.
Abstract: Objectives: The aim of this study was to evaluate the impact of a consistent and dedicated implantation strategy on long-term outcomes after implantation of bioresorbable vascular scaffold (BVS) in a real-world cohort of patients with a high prevalence of complex lesions. Background: Bioresorbable vascular scaffolds may result in a reduced incidence of late and very-late scaffold thrombosis (ScT) after the complete reabsorption of the scaffold, but this hypothesis is hampered by data from RCTs that showed a higher than expected incidence of late events. However, these studies did not adopt a dedicated implantation technique, that proved to be fundamental in reducing the incidence of adverse events. Methods: 573 consecutive patients (912 lesions) treated with bioresorbable scaffolds between May 2012 and December 2014 were enrolled in 3 high-volume centers that used a dedicated implantation strategy from the beginning. Primary endpoints were target-lesion failure (TLF) and definite and probable ScT. Secondary endpoints included myocardial infarction, target-lesion and target-vessel revascularization. Results: The registry enrolled a high complexity subset of lesions (69.4% of type B2 or C lesions; 10.3% of severe calcific lesions; 26.1% of bifurcations). Predilatation was performed in almost all cases (99.2%); intracoronary imaging was liberally adopted (37.3%). Mean scaffold length was 42.9 ± 27.4 mm per patient, and post-dilation with a 1:1 high-pressure (22 ± 3.5 atm) balloon was performed in 99.9% of lesions. Median follow-up (available for 98.6% of patients) was 981 days (IQR 802–1133). Overall incidence of ScT was reassuringly low: three thrombotic events occurred during the first year (0.5%), while only one event ensued in the second year of follow-up, and ScT rate remained stable thereafter up to the fourth year (0.7%). Cumulative TLF rates at 1, 2, 3 and 4 years were 3.0%, 6.0%, 7.8% and 12.2%. Conclusions: These long-term results from a complex "real-world" population appear to be reassuring as regards to the incidence of ScT and TLF when BVS are implanted by experienced operators with a dedicated implantation technique. Highlights: Recent studies showed higher than expected incidence of scaffold thrombosis. Large registries highlighted the importance of a dedicated implant technique. The performance of this dedicated technique was tested in this large registry. The incidence of scaffold thrombosis was reassuringly low (0.7% at 4 years). Dedicated technique has a key-role in bioresorbable scaffolds implantation.